A case study of the Narmada River system in India with particular reference to the impact of dams on its ecology and fisheries. Issue 1 (3rd April 2017) - Bhaumik, Utpal; Mukhopadhyay, M. K.; Shrivastava, N. P.; Sharma, A. P.; Singh, S. N.
Abstract : Narmada, the oldest river system in India, originates from Amarkantak in Madhya Pradesh, flows east-west, and joins with the Gulf of Cambay on the Arabian Sea. The river drains 45.64 km 3 of annual run-off and a series of dams was proposed to hold some of its water resources for multipurpose use. Currently, three dams have been built in Madhya Pradesh and one is under construction in Gujarat. A comparison of pre- and post-impoundment eco-environment and fisheries revealed changes in water quality, productivity, and aquatic flora and fauna of the river system. Among the fish, species like Tor tor, Labeo fimbriatus and Labeo dyocheilus suffered most. The percentage contributions to total yield of Carp, Catfish, and miscellaneous groups have significantly changed, indicating falls of 17%, 36% and an increase of 410%, respectively. Percentage contributions to catches of Macrobrachium rosenbergii and Tenualosa ilisha have also declined by 46% and about 75% in the estuarine stretch of the river system. Suitable conservation measures for sustenance and development of fishery have been suggested.